IMPLEMENTASI WIRESHARK DALAM MELAKUKAN PEMANTAUAN PROTOCOL JARINGAN: Studi Kasus : Intranet Jurusan Teknologi Informasi Universitas Udayana - I Putu Agus Eka Pratama; Putu Adhika Dharmesta (Institute of Computer Science (IOCS), 2019)
Wireshark is a leading open source tool that is widely used to analyze and troubleshoot network problems, allowing us to find out about network problems. The development of Wireshark evolved thanks to the contribution of volunteer network experts around the world and is a continuation of the project started by Gerald Combs in 1998. This monitoring covers the flow of protocol that is being used by networks and computers. This test will implement Wireshark as an application to monitor computer communication networks to see and process the results of network monitoring with case studies on the intranet of the Information Technology Department of the Faculty of Engineering, Udayana University